Pelatihan Integrasi STEM dalam Pembelajaran Pada Kelompok MGMP Fisika SMA Kota Langsa - Dona Mustika; Hasby Hasby (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
STEM education is a way out to create quality and competitive human resources in the 21st century world of work. However, the current STEM movement in Indonesia is still minimal. This is partly due to the lack of understanding of teachers about STEM education itself. Obtained from the results of interviews with the head of the Langsa City High School Physics MGMP, teachers do not yet know how to integrate STEM into learning, and there are no workshops or trainings that provide knowledge about STEM. Therefore, in this activity, a workshop by STEM integration training in Physics learning will be held for teachers in the Physics MGMP (Senior High School) group at Langsa City. Activities are carried out by providing STEM-related materials, preparing STEM-based learning tools by teachers, and evaluating activities. Measurement of the achievement of this activity is carried out through data collection using a questionnaire. The results from this training activity are an increase in the understanding of Physics teachers about the concept of STEM education and the selection of models for STEM learning.